Emotions in the workplace: can shame increase productivity levels? - Martinez, L. F.; Ferreira, A. I.; Cunha, J. V. (Pessoas e Sintomas, 2011)
In this paper, we focus on an unpleasant emotion – shame – that has profound negative psychological and behavioral consequences. Research has documented it as a “social withdrawal” emotion, as ashamed people tend to hide from others. However, shame can also have a positive side, by motivating people to work harder in an organizational context. We propose a dynamic model of the influence of shame in productivity levels. Lastly, we discuss some implications to management.